Managerial Career Concerns and Corporate Tax Avoidance: Evidence from the Inevitable Disclosure Doctrine* - Li, Ningzhong; Shevlin, Terry; Zhang, Weining (Contemporary Accounting Research, 2022)
ABSTRACT While managers' career concerns have been shown to be influential in shaping their decisions, there is little evidence of the impact such concerns may have on managers' tax avoidance incentives. This study examines the causal effect of managers' career concerns on tax avoidance using the staggered recognition by state courts of the inevitable disclosure doctrine (IDD), a trade secret protection doctrine that places greater restrictions on managers from joining or forming a rival company. We argue that the IDD recognition increases the cost of job loss for managers whose current jobs may be in jeopardy, thereby increasing their incentive to avoid taxes in order to positively change their current employer's evaluation of their ability. The IDD recognition also reduces outside opportunities for high‐ability managers, and thereby reduces their incentive to avoid taxes in order to positively change external employers' evaluation of their ability. Using a difference‐in‐differences design, we provide evidence consistent with these predictions. We further show these effects are stronger for CEOs in their early years of service in the focal firms when the market is more uncertain about their ability. Our findings suggest that managers take into account the impact of tax avoidance on their career outcomes when making tax avoidance decisions.